Seafaring expeditions to Punt in the Middle Kingdom : excavations at Mersa/Wadi Gawasis, Egypt - Bard, Kathryn A. (Culture and History of the Ancient Near East, 2018)
In the 12th Dynasty (ca. 1985-1773 BC) the Egyptian state sent a number of seafaring expeditions to the land of Punt, located somewhere in the southern Red Sea region, in order to bypass control of the upper Nile by the Kerma kingdom. Excavations at Mersa/Wadi Gawasis on the Red Sea coast of Egypt from 2001 to 2011 have uncovered evidence of the ancient harbor ( Saww ) used for these expeditions, including parts of ancient ships, expedition equipment and food - all transported circa 150 km across the desert from Qift in Upper Egypt to the harbor. This book summarizes the results of these excavations for the organization of these logistically complex expeditions, and evidence at the harbor for the location of Punt.